Effectiveness of Video Instructional Techniques (VIT) On Learning Outcomes of Vulnerable Learners in Junior Secondary Schools - Akande, Rotimi M.; Adebanjo, Adetayo A. (West African Journal of Open and Flexible Learning, 2023)
This study examined the impact of video instructional techniques on enhancing the learning outcomes of vulnerable learners in secondary schools. In the context of evolving teaching methods and the imperative to address diverse learning needs, the study explored the effectiveness of instructional videos compared to traditional face-to-face instruction. A quasi- experimental design was employed, involving pre-test and post-test measures for both experimental and control groups. The findings revealed that instructional videos significantly improved the learning outcomes of vulnerable learners. Additionally, the study highlighted the positive influence of instructional videos on learners’ retention abilities. This research contributes to the discourse on innovative teaching strategies, particularly their efficacy in catering to diverse student needs and enhancing educational outcomes. Résumé : Cette étude a examiné l’impact des techniques pédagogiques par vidéo sur l’amélioration des résultats d’apprentissage des apprenants vulnérables dans les écoles secondaires. Dans le contexte de l’évolution des méthodes d’enseignement et de l’impératif de répondre aux besoins d’apprentissage divers, l’étude a exploré l’efficacité des vidéos pédagogiques par rapport à l’enseignement traditionnel en face-à-face Un modèle quasi-expérimental a été utilisé, impliquant des mesures de pré-test et de post-test pour les groupes expérimentaux et les groupes de contrôle. Les résultats ont révélé que les vidéos pédagogiques amélioraient de manière significative les résultats d’apprentissage des apprenants vulnérables. De plus, l’étude a mis en évidence l’influence positive des vidéos pédagogiques sur les capacités de rétention des apprenants. Cette recherche contribue au débat sur les stratégies d’enseignement innovantes, en particulier leur efficacité pour répondre aux divers besoins des étudiants et améliorer les résultats éducatifs. Mots-clés : Techniques pédagogiques par vidéo, apprenants vulnérables, enseignement innovant, résultats d’apprentissage